Factors Related to Ground Support Equipment (GSE) Damage (Case Study PT Gapura Angkasa Makassar): Faktor-Faktor yang Berhubungan dengan Kerusakan Ground Support Equipment (GSE) (Studi Kasus PT Gapura Angkasa Makassar) - A. Ferina Herbourina Bonita; Rendhar Putri Hilintang; Ummu Kamilah; Amilah Eka Putri (Universitas Muhammadiyah Palu, 2025)
Human factors or work behavior, characteristics or work environment factors, equipment and material factors and work method factors are sources that cause accident risk. PT Gapura Angkasa Sultan Hasanuddin Airport has hundreds of employees, in the GSE Division. Judging from the process during operation, GSE is not free from danger and risk. This indicates that there is a cause of damage to the GSE so that the stability of workers continues to run well and the smooth operation of aircraft and passengers. This research aims to determine factors related to damage to Ground Support Equipment (GSE) at PT Gapura Angkasa Makassar. This research method is an analytical observational study using a cross sectional research design. The population in this study is the total number of engineering workers.The sample in this study consisted of 44 GSE operators who were determined using the total sampling method where all members of the population were used as samples and the data collected was analyzed using the chi squared test. The results of the analysis using the chi squared test showed that the knowledge variable was not related to GSE damage (p=0.143), attitudes were not related to GSE damage (p=0.062), actions were related to GSE damage (p=0.039), unsafe action (unsafe action) not related to GSE damage (p=0.277), and unsafe conditions not related to GSE damage (p=0.038). It can be concluded that the attitude and unsafe condition variables have a relationship to GSE damage and the knowledge, action and unsafe action variables have no relationship to GSE damage. It can be concluded that the unsafe action variable is an intervening variable for the influence of work shifts, work fatigue, on work accidents. It is hoped that future researchers will expand the population and sample size to obtain better research results